Gravity-Vector Induces Mechanical Remodeling of rMSCs via Combined Substrate Stiffness and Orientation - Zhang, Chen; Lü, Dongyuan; Zhang, Fan; Wu, Yi; Zheng, Lu; Zhang, Xiaoyu; Li, Zhan; Sun, Shujin; Long, Mian (Frontiers in Bioengineering and Biotechnology, 2022)
Distinct physical factors originating from the cellular microenvironment are crucial to the biological homeostasis of stem cells. While substrate stiffness and orientation are known to regulate the mechanical remodeling and fate decision of mesenchymal stem cells (MSCs) separately, it remains unclear how the two factors are combined to manipulate their mechanical stability under gravity vector. Here we quantified these combined effects by placing rat MSCs onto stiffness-varied poly-dimethylsiloxane (PDMS) substrates in upward (180°), downward (0°), or edge-on (90°) orientation. Compared with those values onto glass coverslip, the nuclear longitudinal translocation, due to the density difference between the nucleus and the cytosol, was found to be lower at 0° for 24 h and higher at 90° for 24 and 72 h onto 2.5 MPa PDMS substrate. At 0°, the cell was mechanically supported by remarkably reduced actin and dramatically enhanced vimentin expression. At 90°, both enhanced actin and vimentin expression worked cooperatively to maintain cell stability. Specifically, perinuclear actin stress fibers with a large number, low anisotropy, and visible perinuclear vimentin cords were formed onto 2.5 MPa PDMS at 90° for 72 h, supporting the orientation difference in nuclear translocation and global cytoskeleton expression. This orientation dependence tended to disappear onto softer PDMS, presenting distinctive features in nuclear translocation and cytoskeletal structures. Moreover, cellular morphology and focal adhesion were mainly affected by substrate stiffness, yielding a time course of increased spreading area at 24 h but decreased area at 72 h with a decrease of stiffness. Mechanistically, the cell tended to be stabilized onto these PDMS substrates via β1 integrin–focal adhesion complexes–actin mechanosensitive axis. These results provided an insight in understanding the combination of substrate stiffness and orientation in defining the mechanical stability of rMSCs.